Effects of Targeted Interventions on Lifestyle Modifications of Chronic Kidney Disease Patients: Randomized Controlled Trial. (October 2013) - Teng, Hsiu-Lan; Yen, Miaofen; Fetzer, Susan; Sung, Junne-Ming; Hung, Shih-Yuan
Targeting interventions to an individual's readiness to modify lifestyle factors, specifically diet and exercise behaviors, may delay chronic kidney disease (CKD) progression. This study examined the effects of a targeted Lifestyle Modification Program based on the readiness to change health-promotion lifestyle behaviors, renal protection knowledge, and physical indicators of patients with early CKD. A repeated-measures design randomized 160 CKD patients from four southern Taiwan outpatient nephrology clinics into control and intervention groups. Data were collected five times over a year with a participant retention rate of 64.4%. The intervention group demonstrated significant improvement with regard to diet behavior modifications. Compared with the control group, the intervention group showed a significant improving trend of renal function protection knowledge, stress management, and interpersonal relations. Targeted interventions for patients in the early phases of CKD promotes adherence to proper diet, exercise behavior, and positive lifestyle modifications.